Behavioral and Subjective Effects of Reducing Nicotine in Cigarettes: A Cessation Commentary. (23rd December 2019) - Piper, Megan E; Drobes, David J; Walker, Natalie
Abstract: This commentary addresses critical questions regarding the impact of the reduction of nicotine on changes in smoking behavior. There appears to be moderate evidence that use of reduced nicotine cigarettes (RNC) increases the likelihood of making a quit attempt among smokers unmotivated to quit and among smokers motivated to quit who also used nicotine replacement therapy (NRT). There was limited evidence that RNC combined with NRT increased smoking abstinence, regardless of motivation to quit. Several plausible mechanisms via which RNC may influence smoking behavior, including reducing dependence, are reviewed. The moderate evidence that abrupt reduction in nicotine reduces self-reported dependence as well as smoking behavior and likelihood of relapse is also reviewed. The data reviewed here suggest that abrupt switching to, and extended use of, RNC can reduce cigarette dependence and several related constructs, including the ability to quit smoking. The data reviewed in this commentary suggest that abrupt reduction in the level of nicotine in combustible cigarettes could reduce smoking behavior, nicotine dependence, and other related constructs and increase quit attempts and eventual smoking cessation.